EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE CONCEPT MAPPING GROUP RESUME(CMGR) DAN CONCEPT MAPPING (CM) DITINJAU DARI MOTIVASI PESERTA DIDIK - Arlin Astriyani (Jurnal Pembelajaran Matematika, 2013)
Abstract: This study aimed to investigate: (1) which type more effective, a CMGR type, a CM type, or a Direct Instruction, (2) which one had a better mathematics achievement, students who had high, middle or low motivation students, (3) in each CMGR type, a CM type or Direct Instruction model, which one had a better mathematics achievement, students who had high, middle, or low motivation (4) in each motivation students (high, middle and low), which one more effective, students taught by a CMGR type, a CM type, or a Direct Instruction. We used the fifth grade students of elementary school in Nusawungu Subdistrict as the population. This study was a quasi experimental research by 3 x 3 factorial design. The instruments used to collect data are prior ability test in mathematics, a motivation questionnaire and achievement test in mathematics. The data were analyzed using unbalanced two ways analysis of variance. Based on the data analyzed, it was concluded that: (1) a CMGR type had better mathematics achievement than a CM type and a Direct Intruction, and a CM type had better mathematics achievement than a Direct Instruction, (2) the high motivation students had better mathematics achievement than the middle and low motivation students, and the middle motivation students had better mathematics achievement than the low motivation students, (3) for all types of learning model, high motivation students had better mathematics achievement than middle and low motivation students, (4) for high and middle motivation students, a CMGR type more effective than a CM type and Direct Instruction, and for low motivation students, a CM type more effective than a CMGR type and Direct Instruction.Keywords : Concept Mapping Group Resume (CMGR), Concept Mapping (CM), Direct Instruction, Motivation, Mathematics Achievement.